The Resurgence of Islamic Thought: The Reformist Approach of Maulana Wahiduddin Khan - Khalid Hussain Mir (Fakultas Agama Islam Universitas Wiralodra, 2023)
Throughout history, there has been constant change and development within societies, social events, phenomena, and social organizations. One of the progressions and advancements in the West is modernization, which has affected almost the whole world and has emerged as a unique innovation in all expanses of life, such as art, science, philosophy, religion, and technology. The current influence of the relationship between the West and Islam and the resulting change in Islam is a major theme in modern history. As human values ​​become simple commodities, the spirit of education declines. While modernization has many implications, none of these consequences are obvious as it affects every aspect of human existence, including education. Maulana Wahiduddin Khan, a prominent 20th and 21st-century reformer with international inspiration, remarkably in the United States, and the Indian subcontinent, had an assortment of thoughts on this subject. The practice of peace and spiritual education has always been a never-ending endeavour. Keeping up with the latest developments is always a struggle for Islamic spirituality. Also, the present age, which is the modern age of information technology, always collides with Islamic thought. Wahiduddin Khan endeavoured and emphasized reformulating Islamic education and the notion of western. He believes that Islamic education requires a paradigm shift with modern ideas and values. Muslim academicians all over the world have Maulana as an inspiration, with his interpretation of Islam fitting the contemporary scientific environment. He encouraged Muslim academicians to read Islamic scriptures from a modern perspective. Despite Islamic history and western traditions, he was able to critically examine both to create a new approach to dealing with the current issues of Muslims. So, in this paper, an analytical study has been made to revisit the resurgence of Islamic thought and to find out the reformist approaches of Maulana Wahiduddin Khan in the contemporary Muslim World.